Financial Performance Analysis on PT Perkebunan Nusantara I Regional 5 Surabaya Period 2019 - 2023 - Eko Iswan Rusdianto; Muhammad Firdaus; Diana Dwi Astuti (International Journal of Economics, Commerce, and Management, 2025)
This study aims to analyze the financial performance of PT Perkebunan Nusantara I Regional 5 Surabaya for the 2019-202 period. The method used in this research is quantitative descriptive method. To determine the financial performance of PT Perkebunan Nusantara I Regional 5 using financial ratio analysis techniques. The ratio analysis used in this study are liquidity ratios (current ratio, cash ratio and quick ratio), solvency ratios (DER ratio, DAR ratio and LTDtER ratio), activity ratios (total asset turnover, receivable period turnover and inventory turnover) and profitability ratios (GPM, NPM, ROE, ROI and ROA). Quantitative data in this study are in the form of financial statements of PT Perkebunan Nusantara I Regional 5 for the 2019-2023 period. Based on the liquidity ratio, PT Perkebunan Nusantara I Regional 5 in 2019-2023 experienced a significant increase from 2020-2023 and its liquidity was better in 2023. The financial performance of the solvency ratio of PT Perkebunan Nusantara I Regional 5 for the 2019-2023 period shows a healthy and stable condition. The financial performance of the activity ratio of PT Perkebunan Nusantara I Regional 5 for the 2019-2023 period shows efficiency in managing receivables and inventories, but the use and utilization of assets to generate income needs to be improved. The financial performance of the profitability ratio at PT Perkebunan Nusantara I Regional 5 is classified as unfavorable which can increase the Company's losses. In general, the Company's performance for the 2019-2023 period is less healthy.